Feminist trends in distance and hybrid higher education: a scoping review - Rocío Jiménez-Cortés (SpringerOpen, 2021)
Abstract Higher distance education models can be described from the theoretical and practical foundation of feminist pedagogy. The objective of this work is to know what feminist approaches are identified in the pedagogical models adopted by distance and hybrid education at the University and what curricular characteristics they have. The scoping review is carried out on a total of 126 journals bringing together 60 indexed, 30 specialized in gender and 6 in education. The final sample is made up of 10 papers that meet the established inclusion criteria. The review method is based on three phases of collection, description, and analysis with different tasks and the PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) protocol is followed. The results obtained from mixed methodology applied show three perspectives that set trends in distance and hybrid higher education models from feminist approaches: (a) feminist-pragmatist, (b) eco-dialogical feminist and (c) intersectional-technofeminist. These trends show the application of feminist principles to curriculum design and their implementation in distance and hybrid higher education.